A multi-agent model for simulation of public crisis information dissemination. (2016) - Meng, Lingpeng; Kang, Qi; Han, Chuanfeng; Zhang, Bingkui
In the public crisis dissemination process, the government, the media and the public form a complex multifaceted system. Grasping the behavioural characteristics and interactive relationship of the agents serves as the theoretical basis for responding effectively to public crises. This paper sets the agent attributes and behavioural prescriptions on the part of the government, the media and the public, and proposes a multi-agent model to simulate the effective factor of public crisis information dissemination. A variety of scenarios were set up on the Netlogo platform, and the evolution results under different parameters were compared and analysed.